Evaluation of the Surface Integrity and Recast Layer in Electrical Discharge Turning of WC-Co Composites - Mehdi Soleymani (3347741) (2024)
Tungsten carbide (WC) and its composites are typically associated with high hardness and high wear resistance, posing challenges in conventional machining processes like turning. To address the machining difficulties of WC-Co, electrical discharge turning (EDT) was proposed. The rotational speed in EDT is a key factor influencing the machining results; however, conflicting reports exist about its impact on the EDT process. Therefore, the effect of rotational speed on three different machining regimes, including roughing, semi-finishing, and finishing, was investigated using energy-dispersive X-ray spectroscopy (EDX), SEM, and roughness tests. Additionally, elemental mapping was applied to illustrate the element distribution on the machined surface. The results indicated that increasing the rotational speed led to a 10% to 17% decrease in the recast layer thickness and a 14% to 54% reduction in the surface roughness (Ra). Other Information Published in: Micromachines License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/mi15060707